2007
DOI: 10.1177/0898010107301616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Holistic Nursing Course

Abstract: A study of an undergraduate course in holistic nursing was conducted to determine its impact on personal and professional health care practices. A mixed method design was used to examine responses on a sample of 200 participants. Results indicated a positive personal impact with continued application of concepts into professional health practices. Personal and professional nursing practices were influenced from 1 to 7 years after completing the holistic nursing course. After introduction of the concepts of sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…Classes in self-care, on the other hand, have been shown to make short-term improvements in students' lifestyles (Stark, Manning-Walsh, & Vliem, 2005;Yeh, Chen, Wang, Wen, & Fetzer, 2005). How long the benefits last from such courses remains in question, but one study found that positive effects persisted up to 7 years (Downey, 2007). Students seem to understand that courses in self-care could facilitate their success, yet these courses are not consistently required in nursing curricula (Gardner, Deloney, & Grando, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Classes in self-care, on the other hand, have been shown to make short-term improvements in students' lifestyles (Stark, Manning-Walsh, & Vliem, 2005;Yeh, Chen, Wang, Wen, & Fetzer, 2005). How long the benefits last from such courses remains in question, but one study found that positive effects persisted up to 7 years (Downey, 2007). Students seem to understand that courses in self-care could facilitate their success, yet these courses are not consistently required in nursing curricula (Gardner, Deloney, & Grando, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students who participated in a holistic health class were surveyed roughly 1-7 years after the course and rated their feelings towards the class. The study found that 52% of the students use the learned information "frequently" in their personal lives and 42% in their professional lives [17].…”
Section: Literature Reviewmentioning
confidence: 95%
“…18 19 Mesleki deneyim ve alanında akademik eğitim almış olmanın hemşirelerin hemşirelik yeterliliğini olumlu etkilediği belirtilmektedir. 21 YBÜ'de sorumlu hemşire olarak çalışıyor olma ve yüksek lisans mezunu olma hemşirelerin hemşirelik eğitimi ve yönetimi ile hemşirelik yeterlilik düzeyini arttırmıştır. Literatürde hemşirelik ve profesyonellik üzerine yapılmış çalışmalar incelendiğinde, çalışma sonucumuzla uyumlu olarak yönetici hemşirelerde profesyonellik düzeyinin daha yüksek olduğu bulunmuştur.…”
Section: Bulgular Ve Tartişmaunclassified
“…24 Downey'in çalışmasında da holistik hemşirelikle ilgili bir kurs eğitiminin bireysel ve profesyonel uygulamaları üzerindeki etkisi araştırılmış ve çalışma sonunda eğitimin profesyonel hemşirelik uygulamalarını etkileyen bir farkındalık yarattığı ve hemşirelerin hastaların gereksinimlerini karşılama biçimini etkilediği belirlenmiştir. 21 Türkiye'de yapılan bir çalışmada ise hemşirelerin eğitim düzeyi arttıkça yapılan tıbbi hataların azaldığı saptanmıştır. 25 Yine Türkiye'de yapılan başka bir çalışmada, eğitim düzeylerine göre tıbbi hata tutumları yüksek lisans mezunu hemşirelerin lise, ön lisans ve lisans mezunu hemşirelerden daha olumlu olduğu belirlenmiştir.…”
Section: Bulgular Ve Tartişmaunclassified